Organic functions in a multiple economic entity - localization options. Case study = Funkcje organiczne w wieloczłonowym podmiocie gospodarczym - warianty lokalizacyjne. Studium przypadku - Sobotkiewicz, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
Objective of this study is to identify localizations of fulfilling organic functions within organizational structure in a multiple economic entity and determination of the degree of their centralization and concentration. The nature of this elaboration is theoretical and empirical. The theoretical part presents depending that takes place in management, basic and auxiliary functions. Their inseparability was indicated, they are integrated. What is more, changes in the function areas, for instance caused by use of various management concepts, were shown. In the final part of the theoretical considerations matrix is shown in terms of subject distribution of organic functions. Empirical part focuses on verifying the theoretical assumptions, especially function location. The research had been conducted in all of the subsidiaries of a German automotive industry concern. The following research question was pursued: What organic functions are fulfilled in the subsidiaries and what degree of centralization and concentration is present? Elaboration ends with presentation of conclusions and references.
Keywords: koncern; grupa przedsiębiorstw; jednostka nadrzędna; jednostka zależna; funkcje organiczne; centralizacja; koncentracja funkcji; concern; group of companies; superior unit; corporate headquarters; subsidiary; organic functions; centralization/concentration of functions